Interests of Peru in Arica: Reality and challenges - Cumpa García Naranjo, Luciana (2021)
This article seeks to identify the rights of Peru over Arica according to the Lima Treaty of 1929. In this international agreement, Peruvian rights are recognized over the pier and its use, the building for the Peruvian customs agency, the terminal station of the railway to Tacna and the free transit right. All of them constitute a potentiality that can be exploited economically and commercially for the benefit of the Macro-South Region of Peru and national interests